Preparation of Linalool/Polycaprolactone Coaxial Electrospinning Film and Application in Preserving Salmon Slices - Li, Tingting; Zhang, Xinghui; Mei, Jialin; Cui, Fangchao; Wang, Dangfeng; Li, Jianrong (Frontiers in Microbiology, 2022)
A linalool/polycaprolactone (LL/PCL) antibacterial film was prepared by using a coaxial electrospinning process, and its physical and chemical properties were characterized. The antibacterial film was formed into an active antibacterial gasket, and its effect on salmon preservation was analyzed. The results show that the LL/PCL nanofiber membrane had a well-developed microstructure, and the fiber surface was smooth and uniform. The diameter of the fibers in the PCL membrane without the core material (linalool) was 113.92 ± 23.74 nm. In contrast, the diameter of the coaxial nanofiber membrane with linalool increased, and the diameter of the LL/PCL membranes with 20% and 40% linalool was 220.62 ± 44.01 and 232.22 ± 56.27 nm, respectively. The hydrophobicity and water vapor permeability were enhanced, whereas the tensile strength and elongation at break decreased slightly, while the thermal stability did not differ significantly with the incorporation of linalool. Analysis of the sustained release of linalool showed that the LL/PCL coaxial fiber membranes could release linalool into the reaction system for a long time. The LL/PCL nanofiber film was used to create an antibacterial active gasket for salmon preservation experiments. Sensory evaluation and analyses of the total bacterial count, total volatile basic nitrogen (TVB-N), thiobarbituric acid reactive substances (TBARS), pH, texture (hardness, elasticity, chewiness, and viscoelasticity), water distribution change, and aroma using an electronic nose were used to determine the quality of salmon. It was found that food-grade tinfoil and the PCL gasket had no significant effect on the freshness of salmon, while the active antibacterial gasket samples containing linalool could decrease the rate of decay salmon and effectively prolong the shelf-life of salmon by releasing linalool.